2013
DOI: 10.5194/bg-10-501-2013
|View full text |Cite
|
Sign up to set email alerts
|

Summertime influences of tidal energy advection on the surface energy balance in a mangrove forest

Abstract: Abstract. Mangrove forests are ecosystems susceptible to changing water levels and temperatures due to climate change as well as perturbations resulting from tropical storms. Numerical models can be used to project mangrove forest responses to regional and global environmental changes, and the reliability of these models depends on surface energy balance closure. However, for tidal ecosystems, the surface energy balance is complex because the energy transport associated with tidal activity remains poorly under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 21 publications
4
34
0
2
Order By: Relevance
“…For example, Bergamaschi et al (2011) found that DOC fluxes were 6 times higher during the wet season (September) than the dry season (April), whereas Cawley et al (2013) found that the DOC fluxes were 4 and 10 times higher during the wet vs. dry season (November vs. March) in the Shark and Harney rivers, respectively. Barr et al (2013) showed that forest respiration rates derived from NEE data are greater during the wet than dry seasons.…”
Section: Mangrove Contributing Area and Estuary Carbon Balancementioning
confidence: 99%
“…For example, Bergamaschi et al (2011) found that DOC fluxes were 6 times higher during the wet season (September) than the dry season (April), whereas Cawley et al (2013) found that the DOC fluxes were 4 and 10 times higher during the wet vs. dry season (November vs. March) in the Shark and Harney rivers, respectively. Barr et al (2013) showed that forest respiration rates derived from NEE data are greater during the wet than dry seasons.…”
Section: Mangrove Contributing Area and Estuary Carbon Balancementioning
confidence: 99%
“…The most relevant studies are those from eddy covariance towers measuring atmospheric parameters (e.g., temperature, wind) in and above the canopy simultaneously, along with determinants of forest productivity (CO 2 flux). Using towers in southwestern mangrove forests adjacent to Shark River, the highest productivity rates (shown as a more negative CO 2 flux) were found between 25 and 30°C and optimal photosynthetic rates declined at higher temperatures (Barr et al 2013). Also, the CO 2 Environmental Management uptake or productivity was positively affected by freshwater flows and constrained by salinity higher than 29 ppt (Barr et al 2013).…”
Section: Temperature and Freshwater Flowsmentioning
confidence: 96%
“…Using towers in southwestern mangrove forests adjacent to Shark River, the highest productivity rates (shown as a more negative CO 2 flux) were found between 25 and 30°C and optimal photosynthetic rates declined at higher temperatures (Barr et al 2013). Also, the CO 2 Environmental Management uptake or productivity was positively affected by freshwater flows and constrained by salinity higher than 29 ppt (Barr et al 2013). Elevated CO 2 could ameliorate high temperature and salinity stress in mangrove forests, as the availability of CO 2 for photosynthesis can counter negative temperature effects in terrestrial plants (Sage and Kubien 2007), but research on this potential resilience in mangroves is lacking.…”
Section: Temperature and Freshwater Flowsmentioning
confidence: 97%
“…8); evaporation from the water surface is expected to represent more of the ET balance with net surface flooding. Tidal flooding affects storage and advection of energy in mangrove forests, providing a net sink for heat during high radiation loads (Barr et al, 2013a). In addition, canopy interception from Rookery Bay was estimated at 109 mm year −1 (Twilley and Chen, 1998), or about 10% of ET.…”
Section: Patterns Of Stand Water Use Across Study Sitesmentioning
confidence: 99%